If you always do what you have always done, you will always get what you have always got: commissioning and regulating care homes to prevent abuse. Issue 6 (11th December 2017) - Moore, Steve
Abstract : Purpose: The purpose of this paper is to present a review of some of the fundamental theoretical and contextual components of commissioning and regulatory processes as applied to care home services, revisiting and examining how they impact on the potential prevention of abuse. Design/methodology/approach: By revisiting a number of the theoretical bases of commissioning activity, some of which may also be applied to regulatory functions, the reasons for the apparent limited impact on the prevention of the abuse that occurs in care homes by these agencies are analysed. Findings: The paper demonstrates how the application of commissioning and regulatory theory may be applied to the oversight of care homes to inform proposed preventative strategies. Practical implications: The paper offers strategies to improve the prevention of abuse in care homes for older people. Originality/value: A factual and "back to basics" approach is taken to demonstrate why current strategies that should contribute to tackling abuse in care homes are of limited efficacy.